2005
DOI: 10.1017/s0373463305003188
|View full text |Cite
|
Sign up to set email alerts
|

New Computational Methods for Solving Problems of the Astronomical Vessel Position

Abstract: In this paper, a simplified and direct computation method formulated by the fixed coordinate system and relative meridian concept in conjunction with vector algebra is developed to deal with the classical problems of celestial navigation. It is found that the proposed approach, the Simultaneous Equal-altitude Equation Method (SEEM), can directly calculate the Astronomical Vessel Position (AVP) without an additional graphical procedure. The SEEM is not only simpler than the matrix method but is also more straig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…It can be seen from Table 1 that the observed altitude of Alkaid is as high as 77° 34.9', which exceeds the upper limit of 70° specified in the IM. Hsu et al, (2005) found that for high-altitude observation, an LOP drawn using the IM was shifted due to curvature error, thus resulting in an inaccurate vessel position. It can be seen in Table 2 that all methods but the traditional IM can find the correct vessel position when the first DR position (DR 1) is used; i.e., the distance between the DR position and the actual vessel position is less than 30 NM.…”
Section: Fig 2 Results Of the Two-body Fix By Psomentioning
confidence: 99%
“…It can be seen from Table 1 that the observed altitude of Alkaid is as high as 77° 34.9', which exceeds the upper limit of 70° specified in the IM. Hsu et al, (2005) found that for high-altitude observation, an LOP drawn using the IM was shifted due to curvature error, thus resulting in an inaccurate vessel position. It can be seen in Table 2 that all methods but the traditional IM can find the correct vessel position when the first DR position (DR 1) is used; i.e., the distance between the DR position and the actual vessel position is less than 30 NM.…”
Section: Fig 2 Results Of the Two-body Fix By Psomentioning
confidence: 99%
“…This is also aimed at future celestial navigation education and integration with an Electronic Chart Display and Information System (ECDIS). The data in this case study is taken from Hsu et al [6]. The authors used the Simultaneous Equalaltitude Equation Method (SEEM) to perform a two-body celestial fix.…”
Section: Results Validationmentioning
confidence: 99%
“…Either the assumed position is not needed or the knowledge of an approximate position is sufficient. Some researchers have studied a two-body fix [2,3,5,6,12,14]. It is proposed that at a given time, the astronomical vessel position can be determined by observing circles of equal altitude of two celestial bodies.…”
Section: Spherical Triangle Methods (Stm) and Vector-matrix Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VTS is essential for marine traffic control to be liberated from the existing management methods simply based on wired/wireless communication and to respond quickly to the potentially dangerous situations. The Vessel Traffic Service is to improve the safety and efficiency of vessel traffic, and its marine traffic control service is very important for safe navigation and departure and arrival as a national backbone network [3,10].…”
Section: Introductionmentioning
confidence: 99%